CHCHD4 Regulates Intracellular Oxygenation and Perinuclear Distribution of Mitochondria - Thomas, Luke W.; Staples, Oliver; Turmaine, Mark; Ashcroft, Margaret (Frontiers in Oncology, 2017)
Hypoxia is a characteristic of the tumour microenvironment, and is known to contribute to tumour progression and treatment resistance. Hypoxia inducible factor (HIF) dimeric transcription factors control the cellular response to reduced oxygenation, by regulating the expression of genes involved in metabolic adaptation, cell motility and survival. Alterations in mitochondrial metabolism are not only a downstream consequence of HIF-signalling, but mitochondria reciprocally regulate HIF signalling through multiple means, including oxygen consumption, metabolic intermediates and reactive oxygen species (ROS) generation. CHCHD4 is a redox-sensitive mitochondrial protein which we previously identified and showed to be a novel regulator of HIF and hypoxia responses in tumours. Elevated expression of CHCHD4 in human tumours correlates with the hypoxia gene signature, disease progression and poor patient survival. Here, we show that either long-term (72 hours) exposure to hypoxia (1% O2) or elevated expression of CHCHD4 in tumour cells in normoxia leads to perinuclear accumulation of mitochondria, which is dependent on the availability of HIF-1α. Furthermore, we show that CHCHD4 is required for perinuclear localization of mitochondria and HIF activation in response to long-term hypoxia. Mutation of the functionally important highly conserved cysteines within the CPC motif of CHCHD4 or inhibition of complex IV activity (by sodium azide) redistributes mitochondria from the perinuclear region toward the periphery of the cell and blocks HIF activation. Finally, we show that CHCHD4-mediated perinuclear localization of mitochondria is associated with increased intracellular hypoxia within the perinuclear region and constitutive basal HIF activation in normoxia. Our study demonstrates that the intracellular distribution of the mitochondrial network is an important feature of the cellular response to hypoxia, contributing to hypoxic signalling via HIF activation and regulated by way of the crosstalk between CHCHD4 and HIF-1α.